Whole wheat flour milling: effects of variety and particle size - Turner, Justin B. (Kansas State University, 2012)
Nutrition from whole grains has become an integral part of a healthy diet. Consumers are focused on adding fiber and whole grains to be healthy and want the benefits of whole grain with the taste and appearance of refined flour. A review of current commercial whole wheat flour in the marketplace indicated many options for food processors to use. However, many of these options required processing changes and added ingredients to provide the consumer with a quality product. A milling and baking study was done to compare commercially and experimentally milled whole wheat flours from both white and red wheat varieties. Both white and red wheat varieties were kept identity preserved. Experimental milling was done with a hammer mill and a roll stand to closely replicate the commercial milling process. Baking was done using a sponge and dough method to closely replicate commercial baking conditions. The results showed both particle size and wheat variety impact bake performance of whole wheat flour. The most significant impact appeared to be dependent on the variety of wheat being milled. The milling process also had an impact. As particle size decreased, bake functionality improved. However, some decreased functionality was seen when particle size became very fine. It was concluded that additional work on a commercial flour mill needed to be done to determine if an optimal particle size for milling whole wheat flour exists. Experimental milling equipment was not adequate enough to replicate particle size distributions of commercial whole wheat mills.
Keywords: Whole Wheat; Nutrition; Particle size; Milling; Baking; Food Science (0359)